Alternative Methodologies for Testing CAPM in the Philippine Equities Market - De Ocampo, Pedro, Jr B. (Philippine Management Review; Vol 11 (2004), 2016)
The two approaches of validating CAPM are tested using monthly data of stock returns in the Philippine market.  Results indicate that the conditional relationship proposed by Pettengill, Sundaram, and Mathur (1995) perform better than the Fama and Macbeth (1972) approach in explaining risk return trade-off.  Furthermore, the ability of beta in explaining asset returns is revived.